Dream recall frequency and sensory-processing sensitivity - Schredl, Michael; Blamo, Agnes Elisabeth; Ehrenfeld, Felix; Olivier, Pauline Sophie (Dreaming, 2022)
The lifestyle hypothesis of dream recall emphasizes psychological factors in explaining interindividual differences in dream recall frequency. Recent findings suggest that neurophysiological traits such as default mode network connectivity might also help to explain differences in dream recall. A sample of 1,807 participants (1,008 women, 799 men) with a mean age of 47.75 ± 14.41 years completed an online survey including the Highly Sensitivity Person Scale, the Big Five personality questionnaire, and a dream recall frequency scale. The finding of a relationship between aesthetic sensitivity (a subfactor of sensory processing sensitivity) and dream recall frequency supports the hypothesis that neurophysiological traits might also be important in explaining interindividual differences in dream recall. Large-scale studies using, for example, brain imagining techniques will be necessary to link interindividual differences in information processing to differences in dream recall frequency. (PsycInfo Database Record (c) 2022 APA, all rights reserved)